DEVELOPING REALIA IN TEACHING WRITING DESCRIPTIVE TEXT IN JUNIOR HIGH SCHOOL - Supra Cipto; Neni Afrida Sari Harahap (Universitas Negeri Medan, 2016)
This research is aimed to develop a good realia as a media, easy to be learnt, and can be used for teaching writing descriptive text. This study is developmental research uses Sugiyono’s model. The evaluator of the media are three experts. This instruments employed in this study is a questionnaire, interview, and Test (Pre-test and Post-test). The finding of the study is the quality of the developed realia media viewed from the experts is very good (87,2 %). The final product of this realia media is continued with effectiveness exam. The study takes place in MTs. Swasta Al-Jam’iyatul Wasliyah Tembung to the studens of VIII class, academic year 2016-2017. The samples are 40 students which is given a miniature of SIB monument and National monument as realia. Pre-test and Post-test were administrated to measure students’ ability in writing descriptive text before and after using realia. The scoring system was based on five aspects; they are content, organization, vocabulary, language use, mechanics. The result shows that there is an increase of students’ ability in writing descriptive text by using realia as a media. Therefore, the writer suggest to English teacher to develop realia as one of the alternative ways to increase the students’ descriptive text writing ability.